Integrated interaction between Nano, conventional potassium fertilizer and Zeolite on kinetic K-release from calcareous soil - Sarkawt Taha Ahmed; Haifa Sadik Yaseen Akrawi (Zanco Journal of Pure and Applied Sciences, 2023)
Calcareous soil suffers from deficiency in available of potassium due to its high contain of CaCO3. So, it is important to increase the availability of potassium. Potassium release rate constant is an important indicator for the ability of soil to supply potassium. A field experiments in sulaimani governorate was conducted to evaluate the effect of soil amendment with natural zeolite at rate of (0 and 2 t ha-1), three levels of Nano potassium fertilizer (0, 5 and 10 kg ha-1), three levels of conventional fertilizer K2SO4 (0, 100 and 200 kg ha-1 K2O) and their interactions on kinetic of potassium release within 55 days. Results revealed that there was significant effect of application Zeolite on cumulative K-release that increased by 13.27 % relative to the control treatment. the application Nano, conventional K fertilizer and their interaction with zeolite at level of 5 kg ha-1 Nano, 200 kg ha-1 K2O and 10 kg ha-1 Nano + 100 kg ha-1 K2O amendment with 2 t ha-1 zeolites increased the cumulative K-release from 33.55 to 35.35 and 42.45 mg kg-1 respectively as a compared with control (24.00 mg kg-1). Kinetic data were best described by parabolic diffusion, power function and Elovich models. The cumulative K-release rate constants for parabolic models indicated that all types of fertilizers applied to soil gave high and significant increase in rate of K release compared to the control treatment.